2020
DOI: 10.1002/ajpa.24105
|View full text |Cite|
|
Sign up to set email alerts
|

Early life stress and HPA axis function independently predict adult depressive symptoms in metropolitan Cebu, Philippines

Abstract: Objectives: Alterations in adult hypothalamic-pituitary-adrenal (HPA) axis activity have increasingly been linked with early life stress and adult depression, but a limited number of studies have used longitudinal data to explore HPA axis dysregulation as an underlying mechanism driving the long-term depressive impacts of early stressors. Here we address potential long-term impacts of early life, family-based stress on depressive symptoms among young adults in a longitudinal birth cohort study begun in 1983 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 117 publications
(167 reference statements)
1
17
0
Order By: Relevance
“…This is in line with findings from a recent meta-analysis showing non-significant effects of CA on indices of the diurnal rhythm of cortisol [28]. Moreover, a recent longitudinal study also failed to demonstrate a significant association between CA and indices of diurnal salivary cortisol in a large Filipino sample [29]. The exclusive focus on TSST in our review is supported by the capability of this social stressor in provoking cortisol response consistently and effectively with a large effect size as reported in recent meta-analytic reviews (e.g., [30,31]).…”
Section: Introductionsupporting
confidence: 90%
“…This is in line with findings from a recent meta-analysis showing non-significant effects of CA on indices of the diurnal rhythm of cortisol [28]. Moreover, a recent longitudinal study also failed to demonstrate a significant association between CA and indices of diurnal salivary cortisol in a large Filipino sample [29]. The exclusive focus on TSST in our review is supported by the capability of this social stressor in provoking cortisol response consistently and effectively with a large effect size as reported in recent meta-analytic reviews (e.g., [30,31]).…”
Section: Introductionsupporting
confidence: 90%
“…Additional analyses show that COVID-19 knowledge and perceived COVID-19 risk were inversely and significantly related regardless of educational status, childhood trauma, psychiatric risk, coping ability, quality of life, and demographic factors (β = -0.047, p = 0.043, 95% CI [-0.09, -0.003]). An identical logistic regression model showed that the interaction between childhood trauma and perceived risk was not significant, likely due to the non-linearity assumed in logistic models 13 .…”
Section: Resultsmentioning
confidence: 99%
“…Stressful life events and limited resource availability contribute to impaired health and immune function in children and adolescents (Dunkel et al, 2020;Kim et al, 2020;Schmeer et al, 2019;Wickrama et al, 2005;Yiğit et al, 2018). For example, children born in socioeconomically disadvantaged families had higher probabilities to have developmental impairments due to the inability to provide proper nutrition, vaccination, and adequate access to health care (Krams et al, 2019;Lauringson et al, 2020;Rubika et al, 2020).…”
Section: Discussionmentioning
confidence: 99%